CONFLICTS OF FAITH AND SCIENCE IN RON HOWARD'S ANGELS AND DEMONS MOVIE (2009): A SOCIOLOGICAL APPROACH RESEARCH PAPER - MASNINGRUM., INNAYATULLAH ANGGRAHINI (2011)
The subject of the study is Angels and Demons movie by Ron Howard. This study is aimed to show the conflicts of faith and science Angels and Demons movie by using sociological approach. The objective of the study is to analyze the structural elements and to analyze the movie based on sociological approach. The researcher employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the Angels and Demons movie released in 2009. While the secondary data sources are other materials taken from books, journal, and internet related to the study. Both data are collected through library research and analyzed by descriptive analysis. The study comes to the following conclusions. First, based on structural analysis it is evident, Ron Howard wants to convey his idea about the conflict between faith and science that sometimes accord with each other, but occasionally oppose against each other. All of the aspects in this movie support each other, from the characters, mise-en-scene, lighting, cinematography, sound, and editing that make a beautiful unity in the movie. Second, based on the sociological analysis, there is close relation between the movie production and the underlying social reality which reflected conflicts of faith and science.